Developing and Delivering Pedagogically Informed Technology for Meaningful Learning Experiences within Institutions: Action Points for Creating e-learning Centres - Zenios, Maria; Steeples, Christine (Proceedings of the International Conference on Networked Learning, 2004)
The emergence of the information age has allowed the development of networking as a dynamic form of organisation of human activity maximising the explosion in access to information and knowledge. As higher education institutions, being at the core of the network revolution, rush to deploy new technologies, the need to establish sound pedagogical frameworks for enabling authentic learning through technology, becomes even stronger. The aim of this paper is to discuss some of the key aspects concerning the implementation of an e-learning centre within an institution, with an emphasis on the pedagogical principles supporting such an initiative. Our research approach includes a qualitative survey of a set of existing e-learning centres across Europe, looking at their philosophy and organisation. The paper contributes to an understanding of e-learning by advocating a set of action points for setting up and maintaining pedagogically informed e-learning centres.